Osmanlı'dan erken Cumhuriyet dönemine Edirne'de göç ve iskan yönetimi - Tomruk, Hande (My University, 2024)
1877-1878 Osmanlı-Rus Savaşı'ndan II. Dünya Savaşı'nın sonuna kadar devletin göç ve iskân politikaları dahilinde oluşturulan kurumların göç ve iskân sürecine etkisi Edirne örneğinde incelemek amaçlanmıştır. Özellikle Müslümanların göçü ve devletin Tek parti döneminde orta çıkardığı Trakya Umumi Müfettişliği döneminde izlediği politika, Trakya Umumi Müfettişliğinin işleyişi ve Edirne'de göç ve iskân sürecine etkisini incelenmiştir.

After the Ottoman-Russian War of 1877-1878. It is aimed to examine the impact of the state's immigration and settlement policies and related institutions on the migration and settlement process until the end of World War II, in the case of Edirne. For this reason, it is aimed to examine especially the migration of Muslims and the policy followed by the Thrace General Inspectorate, which was established by the state during the single-party period, the functioning of the Thrace General Inspectorate and its impact on the migration and settlement process in Edirne.
Keywords: Edirne; Göç ve iskan Yönetimi Emigrants; Göç, İç; Göçmenler; Immigration and Settlement Management; İskan Sorunu; Migration, Internal; Settlement problem; Thrace General Inspectorate; Trakya Umumi Müfettişliği; Turkey; Türkiye